A study of anxiety of high school students in English classrooms in An Giang province : - Trần, Thị Thanh Hằng (Can Tho University, 2008)
The present study aimed to explore high-school students' anxiety in English classrooms. The results showed that the students had significant anxiety in English classrooms. There were no significant differences in level of anxiety between male students and female students.